Prokrastinasi ditinjau dari Gaya Kepemimpinan Transformasional dan Self Efficacy - Dwi Rio Sudarroji; Fahmawanti Sekaringrum; Leo Trihartantyo (Psyche 165 Journal, 2020)
This study was conducted to determine the relationship between leadership style and self-efficacy on procrastination. The study population amounted to 34 teachers in a public school in Yogyakarta. The analytical method was a multiple linear regression. Data collection devices are a questionnaire scale of procrastination, self-efficacy, and leadership style. The result showed that correlation significant between self-efficacy and leadership style to procrastination was p = 0.007 <0.05 and a correlation coefficient was B = 0.015 to variable leadership style and a correlation coefficient was B = -0.548 to variable self-efficacy. It showed that there is a positive correlation between leadership style and procrastination but just small influence and a negative correlation between self-efficacy and procrastination.